(untitled) (CAHIERS MAGELLANES-NS, 2024)
From the time immemorial Fishes are known to be the one of the cheapest and rich source of protein and other essential nutrients required for the human beings. The knowledge of proximate biochemical composition of fishes is fundamentally important for the application of different processes like postmortem changes, fish quality etc. the study was carried out to determine the biochemical composition of three types fishes, Sardinella longiceps, Stolephorus indicus and Secutor insidiator of Arabian Sea, Uttara Kannada Karnataka. The protein content in Sardinella longiceps (3.68 mg/gm) was observed highest when compared with the Secutor insidiator (2.5mg/gm) and Stolephorus indicus (0.64 mg/gm). The Fat percentage was observed highest in Sardinella longiceps 2.6% per gm followed by 1.2% per gm in Secutor insidiator and 0.8% per gm in Stolephorus indicus, whereas percentage of Moisture was observed highest in Sardinella longiceps 26.5% per gm followed by 20% per gm in Secutor insidiator and 19% per gm in Stolephorus indicus and the percentage of Ash was observed highest in Sardinella longiceps 14.2% per gm followed by 5.2% per gm in Secutor insidiator and 4% per gm in Stolephorus indicus. The fat, moisture and the ash content in the fishes was observed higher percentage in Sardinella longiceps when compared to that of Secutor insidiator and least was observed in Stolephorus indicus. The biochemical composition of these organisms are influenced by factors such as from the surrounding environment, diet, and absorptive capability, and they are essential for maintaining fish health and ensuring food safety for human consumption.